Everyday Revolutionaries : Gender, Violence, and Disillusionment in Postwar El Salvador - Silber, Irina Carlota, 1968- (Book collections on Project MUSE., 2011)
Silber provides one of the first rubrics for understanding and contextualizing postwar disillusionment, drawing on her ethnographic fieldwork and research on immigration to the United States by former insurgents. With an eye for gendered experiences, she unmasks how community members are asked, contradictorily and in different contexts, to relinquish their identities as "revolutionaries" and to develop a new sense of themselves as productive yet marginal postwar citizens via the same "participation" that fueled their revolutionary action."--Book jacket.